Brand Image And K-Pop Celebrity Endorsers Driving Consumer Purchase Decisions: Citra Merek Dan Endorser Selebritas K-Pop Mendorong Keputusan Pembelian Konsumen - Roudlotul Auwalina; Yulita Tri Arini; Ahmita Dwi Gitania; Nur Kholidah; Sigit Hermawan (International Consortium of Education and Culture Research Studies, 2024)
General Background The global proliferation of Korean pop culture has significantly transformed global and local markets. Specific Background Capitalizing on this phenomenon, multinational companies increasingly utilize Asian idol figures and corporate reputation strategies to stimulate buying interest. Knowledge Gap Despite widespread adoption, previous empirical studies present conflicting evidence regarding whether international promotional figures directly dictate consumer choices, particularly lacking comprehensive models that integrate mediating behavioral factors. Aims This study investigates how idol figures and corporate reputation shape buying choices, specifically examining buying interest as a mediating variable among youth fans in Sidoarjo, Indonesia. Results Path analysis reveals that idol figures and corporate reputation positively stimulate buying interest. Interestingly, idol figures do not directly dictate final buying choices, whereas corporate reputation and buying interest possess a significant direct relationship with buyer choices. Furthermore, buying interest successfully mediates the relationship between idol figures and final buyer choices. Novelty This research highlights that idol figures are insufficient as standalone drivers of sales; their presence must necessarily cultivate preliminary buying interest to translate into actual commercial transactions. Implications Marketing practitioners must prioritize long-term corporate reputation and design campaigns that actively foster genuine product curiosity, rather than relying exclusively on the popularity of idol figures to secure immediate commercial transactions. Highlights: Corporate reputation directly dictates final buyer transactions. International music idols fail to directly secure direct sales. Buying interest successfully mediates the pathway from promotional figures to final commercial choices. Keywords: Brand Image, Celebrity Endorsers, Purchase Interest, Consumer Behavior, Commercial Transactions